Wound-Healing Activity of Herbal Ointment Containing the Root Extracts of Astragalus propinquus in Sprague Dawley Rats - Rajavel, Varatharajan; Mustaffa, Fazlina; Rou, Foo Yau; Qi, Lim Jia; Lin, Catherine Khor Khai; Jothi, Mari; Jayabalan, Karthikeyan (Free Radicals and Antioxidants)
Background: Astragalus propinquus is an herb belongs to the family of Fabaceae. Astragalus propinquus is commonly known as Mongolian milkvetch in English and in Chinese it is called huang qi. Astragalus propinquus is a traditional Chinese herbal medicine with ancient origins, derived from the various roots of Astragalus species native to China Mongolia, North America and Korea. A. propinquus possesses cardiotonic, immunostimulant, hepatoprotective and anti-aging activities. The aim of our study was to assess the wound-healing properties of herbal ointment containing the root extracts of A. propinquus in Sprague Dawley (SD) rats. Materials and Methods: A. propinquus roots were collected dried, powdered and extracted with ethanol and methanol for 7 days by cold maceration method. A.propinquus ointment was prepared using wool fat, hard paraffin, cetostearyl alcohol and white soft paraffin. Ointment formulation was applied once daily on the excision wound on SD rats for 20 days. During the study, the animals were weighed on a regular basis every 5 days. Every fourth day after wound formation, wound contraction was measured as a percentage contraction. In the excision wound model, the wound area was measured by tracing the wound margins onto a transparent sheet and assessing it using millimeter-based graph paper. Results: On day 20, the non-treatment group showed a wound contraction was 90.04±1.06 %. The ethanolic extract group and methanolic extract group showed a significant increase in wound contraction which was 98.44±0.99% and 96.63±0.17 % as compared with non-treatment group, moreover the standard drug treatment group also showed the significant contraction with the percentage of 99.88±0.12%. Conclusion: Plant based ointment exhibited shows significant wound healing activity in rat excision wound model.
Keywords: Astragalus propinquus; Plant based ointment; Sprague Dawley rats; Wound healing activity